2016
DOI: 10.13189/ujer.2016.040111
|View full text |Cite
|
Sign up to set email alerts
|

Operating Classroom Aesthetic Reading Environment to Raise Children's Reading Motivation

Abstract: This research aims to explore how preschool educators understand about raising children's reading motivation through operating classroom aesthetic reading environment. With one year qualitative research, sixteen 4-6 years old young were observed and interviewed. The first stage interviews were undergone with environmental guidance. After the physical class reading environment was adjusted into aesthetic perspective, children's reading motivation and attitudes were triggered. The second stage involved themed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Elliott Eisner also gives a special importance to the aesthetic nature of teaching and learning processes, and this is because of its necessity for teachers to acquire a thorough perception and interpretation of classroom events which is obtained only through ingenuity, insight, creativity, and imagination (Eisner 1994, cited in Mehrmo-hammadi, 2010. Also, studies by Girod, Rau, and Schepige (2010), , Chou, Ching Cheng, and Cheng (2016), Medina (2012), and Kokkos (2011) indicate that aesthetic understanding of teaching and learning processes and paying attention to the aesthetic nature of education can prepare the ground for sustainable development of the quality of learning and teaching; however, despite the emphasis of experts and scholars on the necessity of paying attention to the aesthetic components in the teaching process and their major role in improving instructorsí teaching performance, few field studies are available in this area. Meanwhile, the current educational system has ignored the aesthetic dimensions of education and teaching (Aligh, 2011;Alexander, 2000;Yoo, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Elliott Eisner also gives a special importance to the aesthetic nature of teaching and learning processes, and this is because of its necessity for teachers to acquire a thorough perception and interpretation of classroom events which is obtained only through ingenuity, insight, creativity, and imagination (Eisner 1994, cited in Mehrmo-hammadi, 2010. Also, studies by Girod, Rau, and Schepige (2010), , Chou, Ching Cheng, and Cheng (2016), Medina (2012), and Kokkos (2011) indicate that aesthetic understanding of teaching and learning processes and paying attention to the aesthetic nature of education can prepare the ground for sustainable development of the quality of learning and teaching; however, despite the emphasis of experts and scholars on the necessity of paying attention to the aesthetic components in the teaching process and their major role in improving instructorsí teaching performance, few field studies are available in this area. Meanwhile, the current educational system has ignored the aesthetic dimensions of education and teaching (Aligh, 2011;Alexander, 2000;Yoo, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…The literacy skills are now one of the basic human needs (Moterri & Frandell, 2013), even more so -literacy is the very basic skill that is an obligatory prerequisite for inclusion into the modern society (Carreiras, Armstrong & Danubeita, 2018). Literacy is the most important part of the formal education (Chou, Cheng & Cheng, 2016), and not only the ability to read and write by itself, but more so the skill to select useful, necessary and true information for a particular purpose (Anspoka & Tūbele, 2015). A person's literacy skills serve as a clear indicator of his quality of life.…”
Section: The Methods Nd Materials For Promoting Reading Literacy Skilmentioning
confidence: 99%
“…Multimedia presentations create learning opportunities for children to interact tactilely with the whiteboard and also enrich the presentation of resources, giving children the opportunity to engage in multimedia dialogue and interaction [ 19 ]. Through data collection, methods used included observations, interviews, and a review of children's related documents to explore how early childhood educators can enhance young children's motivation to read through manipulating the classroom environment [ 20 ]. The study concluded that thematic reading and shared reading would enhance young children's motivation to read.…”
Section: Related Workmentioning
confidence: 99%